Matematyka

Autorzy:Joanna Czarnowska, Jolanta Wesołowska, Wojciech Babiański, Lech Chańko

Wydawnictwo:Nowa Era

Rok wydania:2014

Wyznacz sumę f+g oraz różnicę f-g 4.6 gwiazdek na podstawie 10 opinii
  1. Liceum
  2. 2 Klasa
  3. Matematyka

`a)` 

`(f+g)(x)=f(x)+g(x)=ul(2x^5)-ul(ul(x^2))+ul(ul(ul(3x^3)))+ul(ul(ul(ul(2))))+ul(ul(ul(x^3)))-ul(2x^5)+ul(ul(x^2))-ul(ul(ul(ul(6))))=4x^3-4` 

`(f-g)(x)=f(x)-g(x)=ul(2x^5)-ul(ul(x^2))+ul(ul(ul(3x^3)))+ul(ul(ul(ul(2))))-ul(ul(ul(x^3)))+ul(2x^5)-ul(ul(x^2))+ul(ul(ul(ul(6))))=4x^5+2x^3-2x^2+8` 

 

 

 

`b)` 

`(f+g)(x)=-3x^3+2x^5-x^6+7x^2+x+4x^5-x^2+x^6-3x^3=6x^5-6x^3+6x^2+x` 

`(f-g)(x)=-3x^3+2x^5-x^6+7x^2+x-4x^5+x^2-x^6+3x^3=-2x^6-2x^5+8x^2+x` 

 

 

 

`c)` 

`(f+g)(x)=0,75x^6+2x^4-0,125x^2+2,5+1/8x^2-1/4x^6+3x^4-3/2=` 

`\ \ \ \ \ \ \ \ \ \ \ \ \ =3/4x^6+2x^4-1/8x^2+2 1/2+1/8x^2-1/4x^6+3x^4-1 1/2=` 

`\ \ \ \ \ \ \ \ \ \ \ \ \ =1/2x^6+5x^4+1` 

`(f-g)(x)=0,75x^6+2x^4-0,125x^2+2,5-1/8x^2+1/4x^6-3x^4+3/2=`  

`\ \ \ \ \ \ \ \ \ \ \ \ \ =3/4x^6+2x^4-1/8x^2+2 1/2-1/8x^2+1/4x^6-3x^4+1 1/2=` 

`\ \ \ \ \ \ \ \ \ \ \ \ \ =x^6-x^4-1/4x^2+4`